Integrasi Nilai- Nilai Islam dalam Kearifan Lokal Nyadran untuk Menumbuhkan Kerukunan dan Toleransi pada Masyarakat Jenar Ngepung - Fauziah, Giska Enny; Aliyah, Nafilah Na’imatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Nyadran has a combination of local culture and religion, especially Islamic and Javanese culture, which respect for ancestors. This ritual also reflects the values of togetherness, mutual cooperation, tolerance and harmony between society. This research aims to integrate Islamic values in the local wisdom of Nyadran tradition to promote harmony and tolerance in society and also to identify how Islamic values can be internalized in the Nyadran tradition without eliminating the essence of local wisdom, as well as its impact on harmony and tolerance between society. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observation, and literature review related to the Nyadran tradition and Islamic teachings on harmony and tolerance. Data analysis was done descriptively by combining cultural and religious perspectives. The results showed that the integration of Islamic values in the Nyadran tradition can be done with a dialogical approach between religious leaders and local traditional leaders. Some Islamic values that have been successfully integrated include the attitude of gratitude, almsgiving, and social care. In addition, it was found that the involvement of all elements of society in the Nyadran event can strengthen the sense of togetherness and tolerance. Harmony is created when the tradition is not only a religious ritual, but also a means of strengthening social relations between society. The conclusion of this research is that the integration of Islamic values in local wisdom such as Nyadran has the potential to become a model for the creation of harmony and tolerance in a multicultural society. This tradition can be a bridge between local cultural identity and Islamic values, which ultimately strengthens social cohesion in the Jenar society.